Synthesis of Chitosan-based Materials with Ester-benzoate Modification and Its Application as An Antimicrobial Agent - Ratnawati, Devi; Wibowo, Risky Hadi; Andini, Vicka; Maryanti, Evi; Kurniawan, Yehezkiel Steven (Pandawa Institute, 2026)
Microbial infections pose serious threats to human health, emphasizing the need to develop effective antimicrobial materials. This study aims to synthesize, characterize, and evaluate the antimicrobial properties of ester vanillin-benzoate (1) and its chitosan-based composite material (2). Furthermore, the synthesized compound was tested for antibacterial and antifungal activities against Staphylococcus aureus, Bacillus subtilis, Escherichia coli, Pseudomonas aeruginosa, and Candida albicans using the Kirby-Bauer diffusion method. The synthesized compounds were effective against S. aureus and B. subtilis but had minimal action against P. aeruginosa, E. coli, and C. albicans. The formation of the Schiff-base composite could increase its antibacterial activity, indicating a synergistic effect arising from the combination of compound 1 and chitosan.